Possibility of using tannins to control greenhouse gas production during digestate storage - Kintl, Antonín; Hammerschmiedt, Tereza; Vítěz, Tomáš; Brtnický, Martin; Vejražka, Karel; Huňady, Igor; Látal, Oldřich; Elbl, Jakub (Waste management (New York, N.Y.), 2023)
The presented paper deals with the testing of a possibility to reduce emissions of undesirable greenhouse gases (CH4, CO2; NOx) and their mixture (biogas) during the storage of digestate using applications of secondary plant metabolites (tannins). The experiment was conducted in laboratory conditions in which the digestate was placed in fermentation chambers. Prior to the fermentation process, preparations were applied to the digestate, which contained tannins: Tanenol Antibotrytis (TA), Tanenol Clar (TC) and Tanenol Rouge (TR) in three concentrations (0.5, 1.0 and 2.0% w/w). The application of these preparations demonstrably affected the production of biogas and the contents of CH4, CO2 and N therein. The application of TR preparation in the concentration of 1.0% and 2.0% significantly reduced the production of biogas as compared with all variants. The preparation further inhibited the process of CH4 development. In contrast, the other preparations with the content of different kinds of TA and TC increased the production of biogas (on average by 15%), CH4 (on average by 7%) and CO2 (on average by 12%) as compared with the control variant and TR variant. These two variants reduced the concentration of N in biogas on average by 38%. Thus, the tested Tanenol tannin preparations can be used in different concentrations either to control emissions of greenhouse gases during the storage of digestate or, in case of increased production of CO2 for its reuse in order to increase methane yields in the process of anaerobic fermentation.
Keywords: Carbon Dioxide; Methane; Biogas; oxid uhličitý; GHG; Greenhouse Gases; Tannins; Biofuels; Digestate; CO(2); biopaliva; methan; skleníkové plyny; taniny; CH(4)